Natural feed additives and bioactive supplements versus chemical additives as a safe and practical approach to combat foodborne mycotoxicoses - Stoev, Stoycho D. (Frontiers in Nutrition, 2024)
This review highlights the possible hazard of mycotoxins occurrence in foods and feeds in regards to foodborne diseases. The possible management of the risk of contamination of foods and feeds with mycotoxins by using natural feed additives, protecting against deleterious effects of mycotoxins or inhibiting the growth of fungi and mycotoxin production, is deeply investigated in the available literature and some effective measures for safe utilization of mycotoxin contaminated feed/food are proposed. The biological methods of decontamination, degradation or biotransformation of mycotoxins are deeply analyzed and discussed. Some natural antagonists against target fungi are also reviewed and a comparison is made with conventional fungicides for ensuring a safe prevention of mycotoxin contamination. The most common and useful chemical methods of mycotoxins decontamination of agricultural commodities or raw materials are also investigated, e.g., chemical additives inactivating or destroying and/or adsorbing mycotoxins as well as chemical additives inhibiting the growth of fungi and mycotoxin production. The practical use and safety of various kind of feed/food additives or herbal/biological supplements as possible approach for ameliorating the adverse effects of some dangerous mycotoxins is deeply investigated and some suggestions are given. Various possibilities for decreasing mycotoxins toxicity, e.g., by clarifying the mechanisms of their toxicity and using some target antidotes and vitamins as supplements to the diet, are also studied in the literature and appropriate discussions or suggestions are made in this regard. Some studies on animal diets such as low carbohydrate intake, increased protein content, calorie restriction or the importance of dietary fats are also investigated in the available literature for possible amelioration of the ailments associated with mycotoxins exposure. It could be concluded that natural feed additives and bioactive supplements would be more safe and practical approach to combat foodborne mycotoxicoses as compared to chemical additives.